Anatomic Preformed Post: Case Report - Lamas Lara, César (2009)
Nowadays, preformed posts are being used frequently, but they do not follow root canal anatomy. Obtaining a more anatomical form of the root canal and reducing the space of the cement, it would help to reduce the possibility of its eviction. This article details the process of making of an anatomical preformed post and the advantages that would represent its clinical use.